Taxonomical study on medicinal plants used by Brunei community in Kampung Benoni, Papar, Sabah / Rafida Razali - Razali, Rafida (2013)
This study was carried through semi-structured interview with respondents via 'snowballing' technique in the village. Specimens of plant that were discussed were collected and identified in Herbarium of the Science & Agrotechnology Complex (KOMSAT), Universiti Teknologi MARA and deposited with unique series numbers. This data is presented in the form of plant key for disease, plant dichotomous key identification and electronic database system. 43 species of medicinal plants were found used by Brunei community (Table 4.1) and diseases treated by the medicinal plants were categorized into 15 type of diseases (Table 4.2).